Tubulointerstitial Biomarkers for Diabetic Nephropathy - Bancha Satirapoj (Journal of Diabetes Research)
Patients with diabetic nephropathy have a higher risk of mortality, mostly from cardiovascular complications. Standard biomarkers including serum creatinine, estimated glomerular filtration rate, and albuminuria are imprecise, do not directly measure renal tissue injury, and are relatively insensitive to small changes in renal function. Thus, availability of novel biomarkers that are sensitive, specific, and precise as well as able to detect kidney injury and predict clinically significant outcomes would be widely useful in diabetic nephropathy. Novel biomarkers of the processes that induce tubulointerstitial changes may ultimately prove to better predict renal progression and prognosis in type 2 diabetes. Recently, certain biomarkers, which were initially identified in acute kidney injury, also have been reported to confer value in evaluating patients with chronic kidney disease. Biomarkers such as cystatin C, kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), angiotensinogen, periostin, and monocyte chemoattractant protein-1 (MCP-1) reflect tubular injury. In this article, we focused on the potential applications of these biomarkers in diabetic nephropathy.